The Moderating Effects Of Intellectual Capital On The Relationships Between Income Diversification And Banking Efficiency In Indonesia - Salsa Femilia Azra; Rachmat Sudarsono (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study examines the impact of income diversification on cost-to-income ratio (CIR) in KBMI 4 banks over the quarterly period 2022–2024, with intellectual capital serving as a moderating variable. Quarterly panel data are analyzed using moderated regression analysis (MRA). The results indicate that income diversification does not have a significant direct effect on banking efficiency. However, intellectual capital significantly strengthens the negative effect of income diversification on CIR. These findings highlight the importance of effective internal resource management in supporting the efficiency of diversification strategies in large-scale banks.